Analisis Kesulitan Belajar Matematika Siswa Sekolah Menengah Pertama pada Era Digital - Safitri, Prahesti Tirta; Syahrudin, Muhammad; Juliana, Adelia Zifa; Raharjo, Sigit (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the mathematics learning difficulties of junior high school students in the digital era. This research employs a descriptive qualitative approach with 25 eighth-grade students as subjects. Data were collected through a questionnaire measuring eight indicators of mathematics learning difficulties and analyzed using descriptive qualitative analysis techniques. The results indicate that students face multidimensional difficulties, including an inability to understand basic concepts, calculation errors, and difficulties in applying formulas. Internal factors, such as low learning motivation and limited comprehension, as well as external factors, such as distractions from digital devices and a lack of variation in teaching methods, exacerbate these challenges. Although digital technology offers various conveniences, its use is often suboptimal due to students' limited ability to utilize these tools effectively.